Influence of gamma irradiation on the molecular dynamics and mechanical properties of epoxy resin. (October 2019) - Chen, Keping; Zhao, Xiuli; Zhang, Fengshun; Wu, Xiaoli; Huang, Wei; Liu, Wen; Wang, Xiaolin
Abstract: The chemical structures, molecular dynamics and mechanical properties of diglycidyl ether of bisphenol-A (DGEBA)/triethylenetetramine (TETA) resins under gamma irradiation and physical ageing have been investigated. Fourier transform infrared (FTIR) spectroscopy results indicated that an amount of amines and oxidized carbonyl-containing products were generated during the irradiation process. The oxidized skin-like layer was confirmed via micro-FTIR, and the thickness of the oxidized layer increased linearly with irradiation dose. Dynamical mechanical analysis and broadband dielectric spectroscopy were used to analyze the molecular dynamics of DGEBA/TETA resins under different irradiation doses. Three distinct relaxations were observed for all polymers. The irradiation process resulted in an increase of local mobility corresponding to β and γ relaxations. The cooperative mobility associated with α relaxation was significantly shifted to lower temperature with irradiation. Meanwhile, α relaxation broadened considerably with increasing irradiation dose, demonstrating an increasingly heterogeneous environment. The gamma irradiation process resulted in an increase of threshold stress, but a decrease of strain at break, which was accounted for a destruction of the cross-linking networks associated with the increase of the heterogeneity environments. Meanwhile, the increase of the flexural and tensile modulus with the irradiation dose was due to the generation of the abundant hydrogen bonds acted as physical cross-linking points. Highlights: The microstructures and macroscopic properties of epoxy resins have been analyzed as a function of gamma irradiation dose. An increase of local and cooperative molecular mobility was observed during gamma irradiation. The threshold stress was reached for lower strains due to an increasingly spatial heterogeneity of the crosslink.